Course Enrollment Patterns in Secondary Schools 1975 to 1987 - Gifford, Antoinette; MPR Associates, Berkeley, CA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1989)
This data handbook presents enrollment statistics for public and private high school graduates for selected years between 1975 and 1987. The data used to generate these statistics were taken from students' high school transcripts. Three data sets were used to generate the statistics in this time series report: the National Assessment of Educational Progress (1987); High School and Beyond (1982); and the National Longitudinal Survey--Youth Cohort (1975-82). The Secondary School Taxonomy was used to organize the data into a consistent framework. There are 147 tables in this report, organized in three series. The first series shows general enrollment trends for students with various demographic characteristics. The second series shows in greater detail the trends in academic enrollments, and the third series presents enrollment trends in the vocational education curriculum. Appendixes provide detailed discussions of the data sources and research methodology. (KC)
Sponsoring Agency: National Assessment of Vocational Education (ED), Washington, DC.
Contract Number: 300-87-0011.
ERIC Note: For related documents, see ED 283 020, ED 290 881, ED 299 412, ED 297 150, CE 053 752-774, and CE 053 783-797.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Education; Credits; Enrollment; Enrollment Rate; Enrollment Trends; High School Graduates; High Schools; School Demography; School Statistics; Secondary School Curriculum; Student Characteristics; Vocational Education; High School and Beyond (NCES) -- National Assessment of Educational Progress -- National Longitudinal Survey Youth Cohort -- Time Series Analysis; Numerical/Quantitative Data